2007
DOI: 10.1007/s10750-007-0582-0
|View full text |Cite
|
Sign up to set email alerts
|

Benthic nutrient fluxes in a eutrophic, polymictic lake

Abstract: Sediment release rates of soluble reactive phosphorus (SRP) and ammonium (NH 4 ) were determined seasonally at three sites (water depth 7, 14 and 20 m) in Lake Rotorua using in situ benthic chamber incubations. Rates of release of SRP ranged from 2.2 to 85.6 mg P m -2 d -1 and were largely independent of dissolved oxygen (DO) concentration. Two phases of NH 4 release were observed in the chamber incubations; high initial rates of up to 2,200 mg N m -2 d -1 in the first 12 h of deployment followed by lower rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…Benthic respiration was coupled to intense NH 4 ? regeneration, with summer rates comparable to those reported for other eutrophic environments, where it can support a relevant fraction of N requirements by primary producers (Nowlin et al 2005;Burger et al 2007). Simultaneously, denitrification efficiency (denitrification : NH 4 ?…”
Section: Metabolism and Internal Processes In Middle Lakesupporting
confidence: 76%
See 1 more Smart Citation
“…Benthic respiration was coupled to intense NH 4 ? regeneration, with summer rates comparable to those reported for other eutrophic environments, where it can support a relevant fraction of N requirements by primary producers (Nowlin et al 2005;Burger et al 2007). Simultaneously, denitrification efficiency (denitrification : NH 4 ?…”
Section: Metabolism and Internal Processes In Middle Lakesupporting
confidence: 76%
“…Anoxic sediments of eutrophic lakes are generally SRP sources to the water column (Moore et al 1998;Nowlin et al 2005;Burger et al 2007). SRP release was measured only during summer in Middle Lake, probably due to reducing conditions in pore waters, as described by the classical P mobility model (Boström et al 1988).…”
Section: Metabolism and Internal Processes In Middle Lakementioning
confidence: 99%
“…Fluxes of P in the Miyun Reservoir or other palaces indicated bottom sediment was an important source of P. It takes up 11-89 % of the external P loading (Table 1 and Table 2). Burger et al (2007) also reported that the mean SRP sediment release rate was three times greater than daily external load. Therefore, internal P loading contributes to reservoirs (or lakes) loading significantly.…”
Section: Comparison With Other Regionsmentioning
confidence: 95%
“…In situ flux chambers result in minimal disturbance to the sediment and overlying water (Burger et al 2007), and to some extent, is the optimal way to get realworld results about the internal flux; However, it is also the most costly way to assess internal loading from sediment. In addition, to measure nutrient flux changes over time, the environment inside the chamber should be the same as that outside the chamber, which is the difficult part of the method.…”
Section: Introductionmentioning
confidence: 99%
“…Several of the lakes have high internal nutrient loadings as a result of organic enrichment of the bottom sediments and remobilisation of bottom-sediment nutrients with eutrophication-driven depletion of dissolved oxygen in bottom waters (White et al 1978;Burger et al 2007;Trolle et al 2008). Lake Okaro, the focus site of the present study, is the most eutrophic of the Te Arawa lakes.…”
Section: Introductionmentioning
confidence: 94%